An update on the treatment of cytomegalovirus infection after allogeneic hematopoietic stem cell transplantation. Issue 11 (2nd November 2019) - Maffini, Enrico; Busca, Alessandro; Costa, Cristina; Giaccone, Luisa; Cerrano, Marco; Curtoni, Antonio; Cavallo, Rossana; Bruno, Benedetto
ABSTRACT: Introduction : Human Cytomegalovirus (CMV) remains a major cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation. Standard treatment options have for long been limited to a small number of effective drugs with significant toxicities. Areas covered : In this manuscript, the authors update a previous review summarizing recent developments in the virology lab and their possible implications for treatment strategies at bedside. In particular, the authors focused on new antiviral drugs already available and under investigation in clinical trials and innovative immunotherapeutic approaches, including adoptive T-cell therapy and vaccines. Expert opinion : Broader knowledge of CMV biology and its relationship with the host immune system is greatly contributing to the development of novel therapeutic approaches. The availability of new drugs, the improved techniques for virological testing and the more accurate patient risk stratification allow to better individualize treatment, limiting toxicity while sparing antiviral effects. The role of immunotherapy is clearly emerging and will further expand our treatment armamentarium.